A new species of the genus Paramesotriton (Caudata: Salamandridae) from Guangxi Zhuang Autonomous Region, southern China - Wu, Yunke; Rovito, Sean M.; Papenfuss, Theodore J.; Hanken, James (Zootaxa, 2009)
A new species of Asian warty newt, Paramesotriton ermizhaoi, is described from Guangxi Zhuang Autonomous Region in southern China. This species is easily distinguished from other congeners by external morphology and osteology. Phylogenetic analyses based on mitochondrial data place P. ermizhaoi as a possible sister taxon to P. hongkongensis and P. chinensis. The number of trunk vertebrae varies from 12 to 13 in the new species. The relationship between P. ermizhaoi and a potentially new Pachytriton species (Pachytriton C), and the Guangxi population of P. chinensis is briefly discussed.